Promotion of school health: a dialogic construction of knowledge with school (Research, Society and Development, 2022)
Objective: to understand the conception of students about health education practice in the school environment and to develop health education actions with elementary school students. Methodology: qualitative study, action-research type, developed with 24 students in the 6th year of elementary school at a Municipal School in Niterói, Rio de Janeiro. Data obtained by the World Café technique and analysis through thematic analysis. Results: two categories emerged: Concepts of health: a view of students and Educational practices in health at school: the demand of students. Participants correlated health with disease prevention. The thematic demands were about the environment, development and hygiene of the body. Playful and dynamic strategies were suggested for learning. In the action phase, three educational practices were developed based on the demand of the students, which were positively evaluated by the students. Final considerations: the educational practice in health with a participative approach, being planned and developed with the use of everyday situations demanded by the participants, is a powerful instrument for health promotion, enabling the dialogic (re)construction of knowledge with students.